Simultaneous profiling of the blood and gut T and B cell repertoires in Crohn’s disease and symptomatic controls illustrates tissue-specific alterations in the immune repertoire of individuals with Crohn’s disease - Mahdy, Aya K. H.; Schöpfel, Valentina; Huppertz-Hauss, Gert; Perminow, Gøri; Tran, Florian; Bang, Corinna; Hov, Johannes R.; Bengtson, May-Bente; Ricanek, Petr; Opheim, Randi; Aabrekk, Tone Bergene; Detlie, Trond Espen; et al. (Frontiers in Immunology, 2025)
IntroductionCrohn’s disease (CD) is a clinical subset of inflammatory bowel disease that is characterized by patchy transmural inflammation across the gastrointestinal tract. Although the exact etiology remains unknown, recent findings suggest that it is a complex multifactorial disease with contributions from the host genetics and environmental factors such as the microbiome. We have previously shown that the T cell repertoire of individuals with CD harbors a group of highly expanded T cells which hints toward an antigen-mediated pathology.MethodsWe simultaneously profiled the αβ and γδ T cell repertoire in addition to the B cell repertoire of both the blood and the colonic mucosa of 27 treatment-naïve individuals with CD and 27 age-matched symptomatic controls.ResultsRegardless of disease status, we observed multiple physiological differences between the immune repertoire of blood and colonic mucosa. Additionally, by comparing the repertoire of individuals with CD relative to controls, we observed different alterations that were only detected in the blood or colonic mucosa. These include a depletion of mucosal-associated invariant T (MAIT) cells and an expansion of TRAV29/DV5-TRAJ5+ clonotypes in the blood repertoire of individuals with CD. Also, a significant depletion of multiple IGHV3-33-IGHJ4+ and IGHV3-33-IGHJ6+ clonotypes in the blood and gut IGH repertoire of individuals with CD.DiscussionOur findings highlight the importance of studying the immune repertoire in a tissue-specific manner and the need to profile the T and B cell immune repertoire of gut tissues as not all disease-induced alterations will be detected in the blood.